Lepromatous leprosy in Bronze Age Oman: micro-CT provides tools for paleopathology in fragmentary and commingled assemblages - Robbins Schug, Gwen; Mahajan, Sangeeta; Carter, Savannah; Leach, Alexandra; Williams, Kimberly D.; Douglas, Khaled A.; Al-Jahwari, Nasser S. (Frontiers in Medicine, 2025)
Paleoradiology uses CT scanning, digital radiography, and 3D imaging to non-invasively characterize the lives and the experience of health and disease for past people. This paper presents an analysis of micro-CT scans of leprosy in three archaeological maxillae from Dahwa, Oman (2500-2000 BCE) to characterize the natural history of disease progression on an ultra-structural level and address environmental and social factors that shaped the experience of health in Arabia during the Bronze Age. The human skeletal remains from Bronze Age Oman present a challenge for paleopathological analysis because they are fragmentary and commingled. We demonstrate microstructural characteristics of lesions in the ventral maxilla and palate that are strongly consistent with a diagnosis of lepromatous leprosy (e.g., atrophy of the anterior nasal spine, resorption of the medial alveolar process, deterioration of the piriform aperture margin, and atrophy of the nasal septum) and the utility of micro-CT for non-invasively characterizing pathology in isolated maxilla from fragmentary, commingled archaeological contexts. The presence of disfigurement, probably resulting from leprosy, in this community provides new evidence about the early migrations of pathogens responsible for leprosy, which despite being an ancient disease is still relatively poorly understood.